Amalan penambahahbaikan Sekolah Menengah Agama Swasta Cemerlang: Persepsi pemimpin sekolah - A. Ghani, Muhammad Faizal; Mat Nasir, Nur Fauzan Azwani; Ayub, Amalina; Mat Jusoh, Ahmad Muhaimin; Elham, Faisol (University of Malaya, 2018)
This study was conducted to explore the excellence practices of school improvement in an outstanding secondary private religious school.This study was based on the perceptions of school leaders. To achieve the purpose of the study, data were collected using qualitative methods. Two school leaders were interviewed. The interview data were analyzed using the thematic analysis method.The results of this study found that four practices of school improvement were implemented in the initial phase.Three school improvement practices were implemented during the implementation phase and three school improvement practices were implemented at the sustainable phase. The implication of this study is that it is necessary to educate the stakeholders to collaborate for the effectiveness of school improvement practices.